2012
DOI: 10.1161/circinterventions.111.964965
|View full text |Cite
|
Sign up to set email alerts
|

Bare Metal Stent Thrombosis and In-Stent Neoatherosclerosis

Abstract: Background-Very late stent thrombosis (VLST) was reported to occur even in patients with bare metal stent (BMS) implantation, although the annual incidence of VLST after BMS was much lower than that after drug-eluting stent implantation. Pathophysiologic mechanisms of VLST after BMS implantation remain largely unknown. . Evidence for fragments of atherosclerotic plaques, such as foamy macrophages, cholesterol crystals, and thin fibrous cap, was more commonly seen in patients with EST (23%) and VLST (31%), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 24 publications
2
40
0
2
Order By: Relevance
“…7,16,[21][22][23] One pathological study demonstrated that in-stent neoatherosclerosis accounts for 15% of VLST in DES and 83% of VLST in BMS. 11 We observed a trend toward more neoatherosclerosis in BMS than in DES (40.5% in DES and 68.4% in BMS; P=0.056).…”
Section: Discussionmentioning
confidence: 99%
“…7,16,[21][22][23] One pathological study demonstrated that in-stent neoatherosclerosis accounts for 15% of VLST in DES and 83% of VLST in BMS. 11 We observed a trend toward more neoatherosclerosis in BMS than in DES (40.5% in DES and 68.4% in BMS; P=0.056).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, although systematic in vivo imaging data are not available for BMS, it is reported that more than one third of these patients present with acute coronary syndromes 5 and have evidence of atherosclerotic plaque within aspirates of definite stent thrombosis. 6 Taken together, there remains a need to characterizeBackground-Re-endothelialization is delayed after drug-eluting stent (DES) implantation. In this setting, neointima is more prone to become lipid laden and develop neoatherosclerosis (NA), potentially increasing plaque vulnerability.…”
mentioning
confidence: 99%
“…4 However, although systematic in vivo imaging data are not available for BMS, it is reported that more than one third of these patients present with acute coronary syndromes 5 and have evidence of atherosclerotic plaque within aspirates of definite stent thrombosis. 6 Taken together, there remains a need to characterize…”
mentioning
confidence: 99%
“…23 Recently, Yamaji showed that aspiration of the thrombus in 42 patients with very late ST after bare-metal-stent thrombosis showed fragments of atherosclerotic plaques and suggested that disruption of in-stent neoatherosclerosis could play a role in VLST. 24 These observations suggest that neoatherosclerosis may be responsible for VLST in some patients. How often neoatheroscleosis occurs and how often it leads to plaque rupture and thrombosis versus restenosis is not known, and further serial studies are needed.…”
Section: Article See P 584mentioning
confidence: 91%